Neuroma morphology: a macroscopic classification system - Raasveld, Floris V.; Weigel, Daniel T.; Liu, Wen-Chih; Mayrhofer-Schmid, Maximilian; Gomez-Eslava, Barbara; Tereshenko, Vlad; Hwang, Charles D.; Wainger, Brian J.; Renthal, William; Fleming, Mark; Valerio, Ian L.; Eberlin, Kyle R. (Muscle & nerve, 2024)
Introduction/Aims Neuromas come in different shapes and sizes; yet the correlation between neuroma morphology and symptomatology is unknown. Therefore, we aim to investigate macroscopic traits of excised human neuromas and assess the validity of a morphological classification system and its potential clinical implications. Methods End-neuroma specimens were collected from prospectively enrolled patients undergoing symptomatic neuroma surgery. Protocolized images of the specimens were obtained intraoperatively. Pain data (Numeric rating scale, 0-10) were prospectively collected during preoperative interview, patient demographic and comorbidity factors were collected from chart review. A morphological classification is proposed, and the inter-rater reliability (IRR) was assessed. Distribution of neuroma morphology with patient factors, was described. Results Forty-five terminal neuroma specimens from 27 patients were included. Residual limb patients comprised 93% of the population, of which 2 were upper (8.0%) and 23 (92.0%) were lower extremity residual limb patients. The proposed morphological classification, consisting of three groups (bulbous, fusiform, atypical), demonstrated a strong IRR (Cohen's kappa = 0.8). Atypical neuromas demonstrated higher preoperative pain, compared with bulbous and fusiform. Atypical morphology was more prevalent in patients with diabetes and peripheral vascular disease. Discussion A validated morphological classification of neuroma is introduced. These findings may assist surgeons and researchers with better understanding of symptomatic neuroma development and their clinical implications. The potential relationship of neuroma morphology with the vascular and metabolic microenvironment requires further investigation.
Online verfügbar: 19. September 2024
Gesehen am 06.03.2025